339TiPPACIFIC-5: Phase III study of durvalumab after either concurrent or sequential chemoradiotherapy (CRT) in patients with stage III NSCLC. (24th November 2019) - Wu, Y-L; Wang, L; Sendur, M A N; Kim, Y-C; Zhu, Z; Cheng, Y; Li, P; Qin, Y; Macpherson, E; Dennis, P A; Lu, S
Abstract: Background: Non-small-cell lung cancer (NSCLC) represents >80% of lung cancer cases worldwide and 30% of patients (pts) present with Stage III disease. Historically, platinum-based CRT has been the standard of care (SoC) for such pts, yet outcomes are poor. Durvalumab (durva) is a selective, high-affinity, human IgG1 monoclonal antibody that blocks PD-L1 binding to PD-1 and CD80. Results from the PACIFIC trial of durva in pts with locally advanced, unresectable, Stage III NSCLC, who did not progress on concurrent CRT (cCRT), showed significant improvements in progression-free survival (PFS) and overall survival (OS) with durva vs placebo (PFS: HR 0.52; 95% CI 0.42–0.65; P < 0.001; OS: HR 0.68; 99.73% CI 0.47–0.997; P = 0.0025), and similar safety profiles (Antonia et al, NEJM 2017; 2018). Consequently, treatment with durva after CRT, the PACIFIC regimen, is quickly becoming the new SoC. However, the PACIFIC trial only assessed pts who had received cCRT, but due to the higher toxicity of this approach, some patients may be better suited to sequential CRT (sCRT). Therefore, the objective of the PACIFIC-5 (NCT03706690) study is to assess durva post-CRT in a broader population, including pts with NSCLC who did not progress following either platinum-based cCRT or sCRT. Trial design: PACIFIC-5 is a phase 3, randomized, double-blind, placebo-controlled, multicenter study. Approximately 360 pts with histologically or cytologically confirmed Stage III, locally advanced, unresectable NSCLC will be enrolled from China and the rest of the world. Eligible pts have not progressed following definitive, platinum-based cCRT or sCRT, and are in complete response, partial response or have stable disease. Pts are being randomized 2:1 to receive either durva (1500 mg i.v.) every 4 weeks, or placebo, until disease progression, toxicity or withdrawal of consent. The primary endpoint is PFS per blinded independent central review; OS is the key secondary endpoint. Other secondary endpoints include OS24, overall response rate, duration of response, PFS2, PFS12, PFS18, time to distant metastases, pt-reported outcomes, durva pharmacokinetics and immunogenicity, and safety assessments. Recruitment is ongoing. Clinical trial identification: NCT03706690. Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: Y-L. Wu: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self): Eli Lilly; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self): Pierre Fabre; Honoraria (self): Pfizer; Honoraria (self): Sanofi; Advisory / Consultancy: Merck; Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim. Y-C. Kim: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Roche; Research grant / Funding (institution): Boehringer Ingelheim. P. Li: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. Y. Qin: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. E. Macpherson: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. P.A. Dennis: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. All other authors have declared no conflicts of interest.